2020
DOI: 10.1080/22221751.2020.1788995
|View full text |Cite
|
Sign up to set email alerts
|

Brucella melitensis , a latent “travel bacterium,” continual spread and expansion from Northern to Southern China and its relationship to worldwide lineages

Abstract: Brucellosis caused by Brucella melitensis is considered to be one of the most important zoonotic diseases in China. In this study, Conventional bio-typing, MLVA (multiple locus variable-number tandem repeat analysis), and WGS (whole-genome sequencing)-SNP (single nucleotide polymorphism) were used to study the genetic similarity of B. melitensis in northern and southern China and analyze its relationship with worldwide lineages. Currently, the distribution of species/biovars of B. melitensis has obviously chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…Globally, despite the remarkable results achieved by the majority of industrialized countries, where bovine brucellosis has been eradicated or controlled, small ruminant brucellosis remains a problem in some of these countries ( 38 ). Our current study confirmed that B. melitensis is a latent “travel bacterium” that continuously spreads and expands from Northern China to Southern China ( 39 ). From 1970 to 2015, B. melitensis has been the pathogen isolated most frequently in human cases, accounting for more than 99% of Brucella spp.…”
Section: Discussionsupporting
confidence: 82%
“…Globally, despite the remarkable results achieved by the majority of industrialized countries, where bovine brucellosis has been eradicated or controlled, small ruminant brucellosis remains a problem in some of these countries ( 38 ). Our current study confirmed that B. melitensis is a latent “travel bacterium” that continuously spreads and expands from Northern China to Southern China ( 39 ). From 1970 to 2015, B. melitensis has been the pathogen isolated most frequently in human cases, accounting for more than 99% of Brucella spp.…”
Section: Discussionsupporting
confidence: 82%
“…The comprehensive molecular epidemiological and phylogenetic analysis of the B. abortus strains nationwide are useful for improving the surveillance and control program to determine the risk factors associated with brucellosis in humans. In this study, 100 B. abortus were collected from 1953 to 2013, indicating that B. abortus strains have circulated in China for the past several decades, but the strain numbers were lower than those of B. melitensis [29]. This observation is in agreement with a report that B. abortus was a secondary pathogen agent for brucellosis in China [6].…”
Section: Discussionsupporting
confidence: 90%
“…The 85% strains were distributed in traditional and domestic animals breeding developed provinces, providing helpful information for disease control and prevention. However, the distribution range of this species is different from that of the B. melitensis strains, which cover all mainland regions in China [30]. Similarly, the most frequently recorded B. abortus biovar is biovar 3 in the Republic of Kazakhstan.…”
Section: Discussionmentioning
confidence: 86%
“…In this study, 100 B. abortus were collected from 1953 to 2013, indicating that B. abortus strains have circulated in China for the past several decades, but the strain numbers were lower than those of B. melitensis [38]. This observation is in agreement with a report that B. abortus was a secondary pathogen agent for brucellosis in China [9].…”
Section: Discussionsupporting
confidence: 90%
“…The 85% strains were distributed in traditional and domestic animals breeding developed provinces, providing helpful information for disease control and prevention. However, the distribution range of this species is different from that of the B. melitensis strains, which cover all mainland regions in China [39]. Similarly, the most frequently recorded B. abortus biovar is biovar 3 in the Republic of Kazakhstan.…”
Section: Discussionmentioning
confidence: 86%